Analisis Pengaruh Radiasi Matahari Terhadap Cahaya yang Dihasilkan oleh Panel Surya - Sandra Dewi; Annisya Agustina; Zauzza Stabita; Bintang Purba (Edukasi Elita : Jurnal Inovasi Pendidikan, 2025)
Sunlight as a renewable energy source that produces heat energy from solar radiation. Radiation is the propagation of energy without an intermediary substance, so that solar energy can reach the earth's surface through radiation due to the vacuum between the Earth and the Sun. Radiation is the only energy that can propagate through a vacuum and reach the earth's surface through direct radiation, diffuse radiation, and total radiation. Solar panels are devices that can convert sunlight into electricity. The study aims to understand the effectiveness of solar panels in generating electricity, identify factors that affect the performance of solar panels in residential environments, and assess the utilization of Energy from Solar Panels that Can Reduce Monthly Electricity Costs at Home. The research methodology used is qualitative. The results of this study, the utilization of solar panels in residential environments shows varying effectiveness, Environmental factors such as temperature, lighting, cleanliness, and extreme weather conditions play an important role in the performance of solar panels in households, Utilization of solar panel energy in households can reduce monthly electricity costs.